2021
DOI: 10.3389/fpubh.2020.570458
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Feasibility Study of Incorporating Whole Person Care Health Coaching Into an Employee Wellness Program

Abstract: Prior research supports positive health coaching outcomes, but there is limited literature on the integration of employer-sponsored health coaching into employee wellness strategy. The aim of our mixed methods study was to assess feasibility, acceptability, and preliminary efficacy of incorporating a whole-person care model of health coaching into an employee wellness program (i.e., weight loss, smoking cessation) that is made available by an employer-sponsored health plan. For the quantitative study, eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Using tools to support decision‐making and learning new skills in prioritizing self, establishing routines, goal‐setting, problem‐solving, and time‐management were found to be significant facilitators of long‐term behavior change. Similar findings were reported in an employer‐offered pilot study of HWC coaching where goal‐setting, improved personal awareness, and motivation were seen as key values of health coaching (Nelson et al., 2020 ). Some of the skills and tools discussed by participants were acquired via HWC, whereas others were learned more organically through life experiences.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Using tools to support decision‐making and learning new skills in prioritizing self, establishing routines, goal‐setting, problem‐solving, and time‐management were found to be significant facilitators of long‐term behavior change. Similar findings were reported in an employer‐offered pilot study of HWC coaching where goal‐setting, improved personal awareness, and motivation were seen as key values of health coaching (Nelson et al., 2020 ). Some of the skills and tools discussed by participants were acquired via HWC, whereas others were learned more organically through life experiences.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is supported by Nelson et al. ( 2020 ) who found that accountability and self‐efficacy are valuable components of HWC. Within our study, participants who made themselves accountable to others and took personal responsibility for their health had greater success in maintaining healthy behaviors.…”
Section: Discussionsupporting
confidence: 65%
“…The LLUH BREATHE cohort profiled in this report is an open, dynamic cohort of current and former smokers who are continuously incentivised to maintain or attempt tobacco cessation through an ‘opt-in wellness discount’ on the out of pocket cost of their health plan. The initial findings from LLUH BREATHE indicated (1) high rates of participation and 4-month abstinence rates1 and (2) preliminary findings of acceptability of the incentivised health plan model to members and providers 14. Our profile of the cohort after more than 5 years of follow-up identifies a rich data set for inquiry into workplace and health plan-based incentives for achieving long -term abstinence from tobacco among employed adults.…”
Section: Discussionmentioning
confidence: 85%
“…1 The first year cessation rate of LLUH BREATHE participants was also notably high (48% achieved a 4-month point prevalence abstinence) 1. Pilot qualitative data provide preliminary clues that the WHP cohort members and their providers are receptive to the incentivised intervention model 14…”
Section: Findings To Datementioning
confidence: 98%
See 1 more Smart Citation